From Charity to Healthcare Services: Transforming Islamic Philanthropy in Rumah Zakat Indonesia - Windya Puspasari, Herti; Suginarti, Suginarti; Nuryati, Tati (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2020)
This study aims to determine public participation in health services at the Pratama Cita Sehat clinic, East Jakarta. This research was conducted by collecting qualitative data through in-depth interview techniques during October-December 2019. The study results indicate that community participation is relatively high. It is evidenced by the community's involvement during the permit process for the establishment of a clinic, building renovations, and cleaning the clinic location. This participation makes the clinic owned by Rumah Zakat, a philanthropic institution that houses it and belongs to the surrounding community. In addition, the clinic's existence is very beneficial, especially for the poor and the poor, who often find it difficult to access health services.